God and Order in Thomas Aquinas - Brent, James (Acta Philosophica, 2016)
Although the notion of order is everywhere in the thought of Thomas Aquinas, especially in major claims about the starting point of the natural knowledge of God and the final end of the cosmos, works on the metaphysics of Aquinas have not commonly discussed order in an explicit way. After making a point about existential Thomism, the purpose of this paper is to thematize order for our consideration, provide an elementary sketch of a metaphysics of order, and show how the theme of order figures into topics such as the natural knowledge of God, the final end of the cosmos, and wisdom.